Hubungan Antara Motivasi keluarga dengan Perilaku hidup Berseih dan Sehat di SMA 2 Tenggarong - Alia Rahmin; Gusti Adi Nugraha; Farah Mellenia; Farina Meidita; Akhmad Fakhri Fadhillah; Sri Sunarti (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Research Objectives to determine the relationship between family motivation and Clean and Healthy Life Behavior at Senior High School Negeri 2 Tenggarong. This research uses quantitative research with a cross-sectional design. Data were obtained using an electric questionnaire (google form) filled out by respondents, to measure variable family motivation with Clean and Healthy Living Behavior (CHLB). Electric questionnaraire distributed via whatshaap group when filling in, stay together in class and accompanied by researchers. The number of research samples was 188 using the Simple Random Sampling technique. The statistical test in this study used the Spearman test. School-age children are vulnerable to health problems that can affect the process of growth and development and learning achievement. Various diseases often appear and attack school-age children related to CHLB. So that students are the main target who must be able to change behavior and life habits to be healthier, high family motivation is 180 (95.7%), because the start of offline learning so that the family is always reminded about CHBL. Good Clean And Healthy Life amounted to 181 (96.3%). Based on the results of the Spearman rank correlation test, the p-value of 0.001 or p <0.05 means that it can be concluded that there is a significant relationship between family motivation and clean and healthy living behavior at school in Senior High School 2 Tenggarong students. There is a relationship between family motivation and clean and healthy living behavior at Senior High School 2 Tenggarong.